HUBUNGAN KEPUASAN KERJA DENGAN MOTIVASI KERJA GURU TAMAN KANAK-KANAK DI KECAMATAN PAYUNG SEKAKI PEKANBARU - Ida Apriyanti Apriyanti; Wilson '; Febrialismanto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aimed to determine the relationship of job satisfaction and work motivation of kindergarten teacher in Payung Sekaki District of Pekanbaru city. The population in this study were 123 teachers. The sample used in this study were 94 teachers. This study used correlation method to see how much the relationship between independent variables and dependent variable. Thetechnique of collecting data that used  was questionnaire in the form of a Likert scale.The data were analyzed using analysis-scale testing and the statistical methods that used was SPSS for Window Ver. 19.The hypothesis of this study was that there is a positive and significant relationship between job satisfaction and work motivation of kindergarten teacher in Payung Sekaki District of Pekanbaru city.It can be seen from the value of the correlation coefficient of 0.512. The level of relationship between job satisfaction and work motivation included was in the medium category. Determinant coefficient that obtained was r2 = 0.262, that's mean that the job satisfaction have influence on work motivation kindergarten teacher on the amount of 26.2% Key Words:Job Satisfaction, Work Motivation